Tony Thirlwall (21 April 1941 - 8 November 2023) - Esteban Pérez Caldentey; Juan Carlos Moreno-Brid; Anthony P. Thirlwall (PSL Quarterly Review, 2023)
The departure of Tony Thirlwall, a pioneer, renowned scholar, and a generous mentor, is a major loss to economics. This article reviews his main contributions to economics. The article focuses on his approach and method to economics and on his research output in the theory and empirics of growth and development.
Keywords: B22; F02; F32; F41; O11; 330; Balance-of-payments constrained growth; Keynes; open economy; Thirlwall's law; Tony Thirlwall